RESPON MASYARAKAT TERHADAP PEMBANGUNAN JALAN KERETA API DI DESA BAGAN SINEMBAH KOTA KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILR - Ikhsan Budi Setiawan; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Train is kind of land transportation that have function to carrying goods and people so they can move out from one place to another place. Inovation is idea, practice or object that belief it new by people or another unit adoption. Train is also inovation of new technology for society in village of Bagan Sinembah City. Theory that be used is response theory, response is form of perception, reaction and answer. Response that referred in this research is society response to construction of train rail in village of Bagan Sinembah City. Society response to this construction are very good, because in entirety, people has accepted the construction in their village. With expectation that they can get compensation for their area and house that struck by this construction and local people can be involved as worker of the construction. So that the people in there can get income and job. Method of research that be used is descriptive quantitative with taking sample use method total sampling, namely the total number of population in made as respondents research. Technique and data accumulation that be used are observation and interview. The results of the study that the overall respondents agree with the construction of roads or railroads in their village. In the process of compensation until this research is done entering inventory and identification stage. The respondents no one knows about the compensation process, they only hear the issues in other areas about compensation.Key words: Train, Inovation, Response, Construction